(untitled) (Research, Society and Development, 2025)
Background: Natural therapeutic agents, such as Cymbopogon citratus essential oil, have gained prominence for their potential antimicrobial properties. This study aimed to evaluate the antimicrobial activity of the essential oil and hydrolate of Cymbopogon against clinically relevant strains of Candida albicans, Escherichia coli, and Pseudomonas aeruginosa. Methods. Essential oil was extracted using the steam distillation method with a Clevenger apparatus, and prepared in three concentrations (50, 75 and 100%) using Dimethyl Sulfoxide. Component quantification was performed using gas chromatography coupled with mass spectrometry. Antimicrobial activity was evaluated using the Kirby-Bauer disk diffusion technique, employing discs impregnated with essential oil. Pure cultures of microorganisms, including Escherichia coli, Pseudomonas aeruginosa, and Candida albicans isolated from Leukorrhea samples, were utilized. The Welch Test was applied to analyze potential differences in inhibition zones of microorganisms in response to essential oil at different concentrations. Results: The essential oil exhibited a yield of 0.98%, with a yellow coloration, clear appearance, and pH of 5.65. Major compounds identified through gas chromatography coupled with mass spectrometry included Beta Myrcene, 6-Methyl-5-hepten-2-one, Ethanol, 2-(3,3-dimethylcyclohexylidene)-, (Z), (1R)-2,6,6-Trimethylbicyclo [3.1.1] hept-2-ene, Isoneral, and Isogeranial. Antimicrobial activity was observed against all three tested species, where the complete inhibition of C. albicans growth was observed with an inhibitory concentration of 50%. However, the hydrosol exhibited modest antibacterial activity against the tested strains. Statistically significant differences in inhibition diameters were observed for the different studied concentrations (p<0.05). Conclusion: The C. citratus essential oil possesses effective antimicrobial activity, proposing a potential antimicrobial alternative. Therefore, the importance of future investigations to explore its therapeutic applicability is underscored.